2015
DOI: 10.1021/acs.organomet.5b00529
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Thermolysis of Dibenzo-7-dimethylgermanorbornadiene

Abstract: The dibenzo-7-dimethylgermanorbornadiene Me 2 GeA (A = C 14 H 10 ) has been synthesized in one step by treatment of MgA·3THF with Me 2 GeCl 2 in tetrahydrofuran (−35°C ) and isolated in 69% yield. The thermolysis of Me 2 GeA in toluene leads to the effective expansion of the bicyclic framework to the dibenzo-7,8-tetramethyldigermabicyclo[2.2.2]octadiene (Me 2 Ge) 2 A, isolated in 71% yield (based on germanium). The bicyclic compounds Me 2 GeA and (Me 2 Ge) 2 A have been characterized by single-crystal X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…Recently, a convenient route to “masked” phosphinidenes of type F was reported starting with the conveniently generated magnesium anthracenide, MgA·3THF . This one‐step methodology is also amenable to the preparation of “masked” digermene G …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a convenient route to “masked” phosphinidenes of type F was reported starting with the conveniently generated magnesium anthracenide, MgA·3THF . This one‐step methodology is also amenable to the preparation of “masked” digermene G …”
Section: Introductionmentioning
confidence: 99%
“…related small molecules via anthracene elimination at mild temperatures [14][15][16][17][18][19][20]. This strategy has led to successful syntheses of novel inorganic aromatic molecules such as P 2 N 3 − [15] and HCPN 3 − [19], as well as an astrophysically interesting species HCP [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the geometries of RPA compounds have been examined by X-ray crystallography [16,[18][19][20], the intrinsic electronic structure and geometry of gasphase APS − have not been studied, though they are the key molecular properties for fundamental understanding of the bond breaking and forming in producing small molecules via anthracene elimination. Therefore, we carried out a joint NIPES [29], velocity-map imaging photoelectron spectroscopy (VMI-PES) [30], and computational study of APS − , and report our findings in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation of suitable molecular precursors presents a potential entry point to explore the synthetic chemistry for such reactive species and opens new avenues for spectroscopic characterization (9)(10)(11)(12)(13)(14)(15)(16). In the case of SO, a limited number of synthetic precursors have been reported that allow thermal transfer of SO ( Fig.…”
mentioning
confidence: 99%
“…Our group has a longstanding interest in small reactive species, such as P2 (9-11), AsP (12), HCP (13), phosphinidenes (14,15), and dimethylgermylene (16), generated by mild thermal activation of suitable precursors. The driving force of anthracene (C14H10, A) expulsion for the release of highly reactive molecules and subsequent characterization and synthetic transfer has been amply capitalized on (13,14,(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%